STATISTICAL ANALYSIS IN VALUE MEASUREMENT OF THE PROCESS OF LEARNING MATHEMATICS DISKRIT STUDY CASE: ENGINEERING STUDY PROGRAM INFORMATICS STIKOM BANYUWANGI INDONESIA - Moch. Najib; Eko Listiwikono (MAN Insan Cendekia Jambi, 2020)
To determine the final value of a value requires accuracy to see the curve and all the conclusions of the results. Statistical calculations using Minitab make it easier and more complete for processing the value data produced by a lecturer. The method used in quantitative research using literature and documentation by taking the volume value data. To make a conclusion based on the statistical value of the test and the results obtained become a conclusion. With analysis of variance and statistical calculations using this mini tab produces an analysis of measuring the value of learning. The result obtained by the lecturer is by using Minitab statistical calculations to make it easier to process value data and to find out the value statistics easily and accurately.